Enhanced photocatalytic activity for titanium dioxide by co-modifying with silica and fluorine - Yang, S.; Sun, C.; Li, Xin Yong; Gong, Z.; Quan, X. (Elsevier BV, 2010)
F-Si-co-modified TiO2 (FST) samples with different ratios of fluorine to titanium (RF) and silica to titanium (Rx), were successfully synthesized by ultrasound-assisted hydrolysis. The structure and properties of the as-prepared codoped titania were characterized by means of XRD, TEM, XPS, BET, UV-Vis diffuse reflectance spectra and ESR. XRD analysis showed that Si and F atoms prevented phase transition of anatase to rutile and suppressed the growth of titania crystalline. ESR results showed that the concentration of the active species (radical dotOH) on 1 % -FS T(Rx = 10 %) was higher than that on other FST samples and P25 titania. The improvement in photocatalytic activity relative to titania can be achieved by co-modifying fluorine and silica to fabricate FST composite material. The photocatalytic activity of FST powders for decomposition of methyl orange was affected by the content of fluorine and the content of silica. When the ratios of RF and Rx were 1 and 10%, respectively, 1 % -FS T(Rx = 10 %) shows the best among photocatalytic activity, which is much superior to P25 under UV-Vis irradiation. The possible reasons for the high photocatalytic activity of the FST powders were proposed in the paper. In addition, the stability of the FST powders in photocatalytic process was confirmed based on the XPS analysis. © 2009 Elsevier B.V. All rights reserved.